2020
DOI: 10.1177/1751143720912697
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lubratex and vitamin A on ocular surface disorders in ICU patients: A randomized clinical trial

Abstract: Background High prevalence of ocular surface disorders includes eye dryness and corneal ulcer among intensive care unit patients remains an issue. This study aimed to compare the effectiveness of Lubratex ointment and vitamin A eye ointment in preventing ocular surface disorders in intensive care unit patients. Methods A single-center randomized clinical trial was conducted in critically ill patients of vitamin A eye ointment and Lubratex ointment in preventing ocular surface disorders. Forty-one eligible pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some studies used varying concentrations of vitamin A drops 20 while others used ointment. 19 , 21 Alanazi et al presented data that suggested oral vitamin A supplements may improve quality but not quantity of tears. 22 How the pharmacokinetics of different routes of administration and dosing affect vitamin A bioavailability to the ocular surface must be investigated in order to better standardize its use.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used varying concentrations of vitamin A drops 20 while others used ointment. 19 , 21 Alanazi et al presented data that suggested oral vitamin A supplements may improve quality but not quantity of tears. 22 How the pharmacokinetics of different routes of administration and dosing affect vitamin A bioavailability to the ocular surface must be investigated in order to better standardize its use.…”
Section: Discussionmentioning
confidence: 99%